Sistem Otomatis Pompa Air dan Sabun pada Wastafel Pencuci Tangan - Andrizal Andrizal; Yultrisna Yultrisna; Junaldi Junaldi; Tuti Anggraini; Anton Anton (Teknik Elektro Politeknik Negeri Padang, 2020)
Washing hands is an activity that should be routinely carried out by every individual, especially during the COVID-19 pandemic like today. There are many factors that make someone feel lazy and don't want to wash their hands, one of which is not wanting to be bothered by hand washing activities such as taking soap, turning the faucet and others. Experiments have been carried out in the form of testing the response of the sensor to detect the user's hand based on the distance and the reading angle. Furthermore, the ability to set the delay time for rubbing hands is tested to activate the water tap pump for rinsing. Based on the results of trials and analyzes carried out, the sensor response is obtained at a minimum distance of 4 cm and a maximum distance of 140 cm with a view or response area of 1100 horizontal positions and 850 in the vertical position. The water pump and soap pump are active for 3 seconds when the user's hand is detected by the sensor approaching the end of the water tap. The water tap pump comes back on after being delayed for 23 seconds, and the system is able to operate 100% automatically. Thus the minimum time for users to rub their hands for 20 seconds according to health standard protocols can be met.